Analisis Semiotika Lirik Lagu Tanah Pusako - Sumartono Sumartono; Ferdinal Ferdinal; M. Takdir; Jusmita Weriza (STARKI, 2023)
The analysis of this study uses the semiotic analysis of Roland Barthes' model with the use of two-stage significance, namely denotative meaning and connotative meaning. The results that the denotation meaning or the real meaning of Tanah Pusako (inheritance landis) the land where women live in the Minangkabau custom which is inhabited for generations by women. Meanwhile, the connotative or additional meaning of Tanah Pusako is the place where women live for generations, so the additional meaning is that pusako property is an inheritance from the Minangkabau people so that the ownership is not private but belongs to the people so it is forbidden to sell it. As for the myths or culture that has become the ideology or belief of the people regarding Pusako Land is land that belongs to the people so it is not privately owned if someone sells the pusako land, there will be many calamities befalling the person selling the pusako land (among them, will experience poverty, calamity , or being sworn in by the former ancestors who occupied Tanah Pusako so that they will experience a lot of suffering in life). ABSTRAK Analisa penelitian ini menggunakan analisa semiotika model Roland Barthes dengan penggunaan signifikasi dua tahap, yakni makna denotatif dan makna konotatif. Hasil penelitian menunjukkan bahwa makna denotasi atau makna sebenarnya Tanah Pusako adalah tanah yang menjadi tempat tinggal kaum perempuan dalam adat Minangkabau yang dihuni secara turun temurun oleh kaum perempuan. Sedangkan makna konotasi atau makna tambahannya Tanah Pusako merupakan tempat tinggal para kaum perempuan secara turun temurun jadi makna tambahannya adalah harta pusako adalah warisan dari kaum Minangkabau sehingga kepemilikannya bukan pribadi tetapi milik kaum sehingga dilarang untuk dijual. Adapun Mitos atau budaya yang telah menjadi ideologi atau kepercayaan masyarakat mengenai Tanah Pusako adalah tanah milik kaum sehingga bukan milik pribadi apabila ada yang menjual tanah pusako tersebut maka akan banyak terjadi musibah menimpa kepada orang yang menjual tanah pusako tersebut (diantaranya, akan mengalami kemiskinan, musibah, atau disumpahi nenek moyang terdahulu yang menduduki Tanah Pusako sehingga akan mengalami banyak penderitaan hidup).